(untitled) (Annals of Medical Research, 2022)
Aim: Trauma is one of the important causes of mortality and morbidity affecting both the geriatric section of society and the young population. Especially in the geriatric population, the life comfort of patients decreases significantly due to trauma. In the present study, we examined geriatric trauma patients admitted to the emergency department and investigated the most common reasons for admission, trauma regions, and post-traumatic hospitalization of these patients. Materials and Methods: 608 geriatric trauma patients aged 65 and over were studied. The patients were evaluated according to their age and sex. The causes of trauma, trauma regions,existing chronic diseases of the patients, and the number of drugs they regularly used per day were examined. The radiological imaging methods requested for the patients and the branches for which consultation was requested due to the post-traumatic injuries of these patients were investigated. The hospitalization and discharge status of the patients and the clinics where they were hospitalized were examined. Results: The patients consisted of 369 (60.7%) females and 239 (39.3%) males. The most common chronic disease was hypertension (n=214, 35.2%). The most common reason for admission was falling (n=434, 71.4%). Soft tissue trauma was the most common finding in the patients (n=432, 71.1%). The mean age of the patients with fracture or dislocation was significantly higher compared to those with soft tissue trauma. The incidence of fracture or dislocation was significantly higher in femalesthanin males. According to the causes of trauma, the incidence of fracture or dislocation was the highest in fall cases, which was significant. Conclusion: Geriatric trauma patients are most frequently admitted to emergency departments due to simple falls. With simple measures to be taken in these patients, falls and exposure to trauma will decrease, and thus patients’ life comfort will increase significantly.